Literacy and Emotional Intelligence in Informal Learning: Key Competencies for the Era of Industry 5.0 - Gudeta Kebede Asfaw (Journal of Research in Social Science and Humanities, 2024)
This study explores the role of literacy and emotional intelligence as essential competencies in informal learning for Industry 5.0, emphasizing the need for adaptive skills to navigate technological advancements balanced with human values. Using a Systematic Literature Review (SLR) approach, the research analyzed publications from 2021 to 2024 in the Scopus database, focusing on studies that address literacy, emotional intelligence, informal learning, and critical competencies for Industry 5.0. Findings reveal that social-emotional skills, digital literacy, and future literacy are foundational for preparing individuals to thrive in complex work and social environments. Evidence suggests that early development of social-emotional learning (SEL) enhances cognitive and interpersonal skills, fostering resilience and adaptability. Informal learning through social activities, sports, and future-oriented reflections strengthens competencies in self-regulation, empathy, and critical thinking, which are essential in rapidly changing contexts. The study recommends integrating SEL into both formal and informal curricula, promoting digital and emotional literacy training, embedding future literacy, and enhancing community-based activities. These strategies can better equip individuals for the collaborative and adaptive demands of Industry 5.0, bridging the gap between technical expertise and human-centred skills.